APEKSIFIKASI MENGGUNAKAN BIODENTINE PADA GIGI INSISIVUS SENTRALIS PASCA AVULSI: CASE REPORT - Damara, Ovy Prima; Maranantan, Helga Anindyastika; Nisa, Nela Khairun; Nelirda, Muhammad Ikhsan (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Introduction: Permanent tooth avulsions occur in 0.5%–16% of all dental injuries. Treatment for avulsions includes replantation followed by root canal treatment to reduce extraoral dry time and achieve a good prognosis. Avulsions in permanent teeth stifle vascular circulation, leading to necrosis. Necrosis in immature permanent teeth results in incomplete apical closure. Such cases require apexification treatment to ensure a hermetic root canal treatment.Aim: The purpose of this case report is to describe apexification treatment for an avulsed immature maxillary central incisor using biodentine.Case and Management: This case report describes the case of a 12-year-old boy with a complaint of a loose tooth due to a fall, 3 hours before arriving at RSGM Prof.Soedomo UGM. The patient arrived with the tooth soaked in saline. The socket was cleaned followed by replantation and splinting for 4 weeks. Four weeks later, root canal treatment and apexification using biodentine were performed. The patient was instructed to return for a follow-up after six months. The results of clinical and radiographic examinations showed good filling, no root resorption, and no complaints from the patient.Discussion: Apexification is a method for creating a calcification barrier on non-vital teeth with open apices. In this case, a one-step apexification procedure was performed to obtain an apical plug using biodentine. Biodentine exhibits excellent biocompatibility, hydrophilic properties, greater sealing ability, and shorter setting times.Conclusion: Biodentine can be used for apexification treatment of avulsed immature teeth and has demonstrated good efficacy in forming an apical barrier.